Synthesis and characterization of ZSM-5 zeolite as catalyst in Claisen-Schmidt condensation reaction - Nik Rohani, Nik Mustapa (2012)
ZSM-5 zeolite is one type of heterogeneous catalyst which obtained in the solid form. There are several advantages of heterogeneous catalyst in the chemical reaction compared to homogeneous such cost reduction, environmental friendly and easy to separate. In this study, ZSM-5 zeolite was synthesized using hydrothermal method utilising rice husk ash (RHA) which is agriculture waste of silica source. Then, the prepared ZSM-5 zeolite with different ratios of Si0 2/Al2 0 3 was characterized by means of Fourier Transformed-Infrared Spectroscopy (FT-IR), Surface Area Analyzer (BET), X-Ray Diffraction (XRD) and Thermogravimetric Analysis (TGA). The catalytic activity of ZSM-5 zeolite was tested by the reaction of acetophenone and benzaldehyde to chalcone at 150 °C and 6 hours. The conversion of the reaction was evaluated using Gas Chromatography-Flame Ion Detector (GC-FID). The conversion to chalcone by HZSM-5(30) give yield up to 82.44 %, Na-ZSM-5(60) give 82.72 %, H-ZSM-5(60) give 82.86 % and Na-ZSM-5(30) give the highest yield of 91.95 %.